A morpho-molecular re-appraisal of Polystigma fulvum and P. rubrum (Polystigma, Polystigmataceae) - Bundhun, Digvijayini; Jeewon, Rajesh; Dayarathne, Monika C.; Bulgakov, Timur S.; Khramtsov, Alexander K.; Aluthmuhandiram, Janith V.s.; Pem, Dhandevi; To-Anun, Chaiwat; Hyde, Kevin D. (Phytotaxa, 2019)
Collections of eleven Prunus specimens infected with Polystigma species from Belarus and Russia yielded two existing taxa: Polystigma fulvum (sexual morph) and Polystigma rubrum (asexual morph). DNA based phylogenies of large subunit nuclear rDNA (LSU) and nuclear ribosomal internal transcribed spacer (ITS) are provided for the first time for Polystigma fulvum and its placement is confirmed within Polystigmataceae. The concatenated LSU and ITS DNA sequence data for P. rubrum, analyzed to infer its potential relationship to other Polystigma species, also show that strains of P. rubrum are segregated into two subclades with sufficient genetic differences. No significant differences in morphology or morphometry among the strains of P. rubrum between the two subclades, especially vis-à-vis the conidiogenous cell and conidium sizes are observed (P>0.05). Subspecies concept of P. rubrum complex is discussed.